A simplified model of dynamic interior cooling load evaluation for office buildings. (5th September 2016) - Ding, Yan; Zhang, Qiang; Wang, Zhaoxia; Liu, Min; He, Qing
Highlights: The core interior disturbance was determined by principle component analysis. Influences of occupants on cooling load should be described using time series. A simplified model was built to evaluate dynamic interior building cooling load. Abstract: Predicted cooling load is a valuable tool for assessing the operation of air-conditioning systems. Compared with exterior cooling load, interior cooling load is more unpredictable. According to principle components analysis, occupancy was proved to be a typical factor influencing interior cooling loads in buildings. By exploring the regularity of interior disturbances in an office building, a simplified evaluation model for interior cooling load was established in this paper. The stochastic occupancy rate was represented by a Markov transition model. Equipment power, lighting power and fresh air were all related to occupancy rate based on time sequence. The superposition of different types of interior cooling loads was also considered in the evaluation model. The error between the evaluation results and measurement results was found to be lower than 10%. In reference to the cooling loads calculated by the traditional design method and area-based method in case study office rooms, the evaluated cooling loads were suitable for operation regulation.